2022
DOI: 10.1002/hbm.26075
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity during orthographic, phonological, and semantic processing of Chinese characters identifies distinct visuospatial and phonosemantic networks

Abstract: While neuroimaging studies have identified brain regions associated with single word reading, its three constituents, namely, orthography, phonology, and meaning, and the functional connectivity of their networks remain underexplored. This study examined the neurocognitive underpinnings of these neural activations and functional connectivity of the identified brain regions using a within‐subject design. Thirty‐one native Mandarin speakers performed orthographic, phonological, and semantic judgment tasks during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Some research posits that the left MFG is intricately connected to general working memory and contributes to the processing of visual attributes ( Kurosaki et al, 2016 ). Alternatively, evidence suggests the MFG is pivotal in assimilating spatial information, necessitating intricate spatial frequency processing, especially when discerning the component relationship of Chinese characters ( Liu C. Y. et al, 2022 ). Although limited studies have examined the association between acupuncture at the LR3 and language, it remains uncertain whether a direct link exists between MTG activation and the treatment of aphasia and related disorders through acupuncture at LR3.…”
Section: Discussionmentioning
confidence: 99%
“…Some research posits that the left MFG is intricately connected to general working memory and contributes to the processing of visual attributes ( Kurosaki et al, 2016 ). Alternatively, evidence suggests the MFG is pivotal in assimilating spatial information, necessitating intricate spatial frequency processing, especially when discerning the component relationship of Chinese characters ( Liu C. Y. et al, 2022 ). Although limited studies have examined the association between acupuncture at the LR3 and language, it remains uncertain whether a direct link exists between MTG activation and the treatment of aphasia and related disorders through acupuncture at LR3.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive processing of these characters involves visuospatial analysis and memory areas where the MFG is actively engaged [24, 42, 43]. Previous studies also suggested that the MFG’s involvement in visuospatial processing might be more pronounced in Chinese due to the logographic nature of its writing system [21, 23, 44, 45], whereas its role in phonological and syntactic processing might be more emphasized in English. These observations confirmed the effectiveness of our approach in tracking the voxel-wise contributions to language production and semantic processing, which also enhances our comprehension of the underlying decoding mechanisms.…”
Section: Discussionmentioning
confidence: 99%